2011
DOI: 10.1614/wt-d-10-00097.1
|View full text |Cite
|
Sign up to set email alerts
|

Miscanthus×giganteusResponse to Tillage and Glyphosate

Abstract: Miscanthus is a perennial, rhizomatous C4 grass grown in the European Union and studied in the United States as a bioenergy feedstock. U.S. farmers might be more willing to grow this perennial species if methods for its control were established. Experiments were conducted from 2007 to 2009 to evaluate methods to control miscanthus. As glyphosate rate increased from 0 to 3.6 kg ae ha−1in a greenhouse trial, miscanthus dry weight decreased. Aboveground biomass in the summer following treatments decreased 82, 77,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…These rhizomes were then susceptible to drying and freezing. These results confirm the conclusion of Anderson et al (2011) that tillage is a critical component in efforts to control M. × giganteus .…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…These rhizomes were then susceptible to drying and freezing. These results confirm the conclusion of Anderson et al (2011) that tillage is a critical component in efforts to control M. × giganteus .…”
Section: Resultssupporting
confidence: 89%
“…Emergence of new M. × giganteus shoots continued throughout the growing season each year. Anderson et al (2011) also observed varying degrees of M. × giganteus regrowth with tillage and glyphosate treatments the year following treatments, indicating that control efforts need to be sustained for more than one season. Similar observations have been reported with other perennial grasses such as Johnsongrass (Parochetti et al, 1975), wirestem muhly (Lingenfelter and Curran, 2007), common reed (Ailstock et al, 2001; Derr, 2008a; Rensburg, 1996), reed canarygrass ( Phalaris arundinacea L.) (Annen et al, 2005), and giant reed (Spencer et al, 2008).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…During this time, carbohydrates, along with the herbicides, are translocated to the rhizomes. However, Anderson et al (2011) did not achieve adequate control of giant miscanthus with glyphosate applied in fall or spring.…”
Section: Introductionmentioning
confidence: 88%
“…In a greenhouse study, Anderson et al (2011) determined that immature giant miscanthus shoot dry weight decreased 59% when treated with an application of glyphosate at 3.6 kg ha −1 . However, in a separate field study, the same researchers found no reduction of shoot numbers when treated with a single application of glyphosate at 2.5 kg ae ha −1 in the spring or fall.…”
Section: Introductionmentioning
confidence: 99%